Responsivitas Badan Penanggulangan Bencana Daerah (BPBD) Dalam Menangani Keluhan Bencana Banjir Di Kota Tanjungpinang - Hena Salsabila Putri; Anggia Sagita; Hajar Ulvia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Responsiveness is a form of feedback and the willingness of service providers to provide support to the community through their services. Responsiveness also refers to the connection between activities and services and the needs and expectations of society. Responsiveness is very important in serving the people because it provides evidence of the organization's capability in recognizing the wishes of the people. This research aims to understand the response capacity of the Regional Disaster Management Agency to flood incidents in Tanjungpinang City. The scope of this research has six criteria, namely: 1) Responding to every customer/candidate who needs to receive services; 2) Staff/equipment provides timely service; 3) Appropriate service personnel/equipment; 4) Personnel/equipment provides services with care; 5) Personnel/equipment performs service immediately; 6) All customer complaints are handled by employees. This study applies qualitative methods combined with qualitative descriptive analysis. The subject of this research is the Head of the Disaster Prevention and Preparedness Division and the Logistics Division. Information retrieval methods include question and answer and note taking. The results of the research show that currently there is starting to be a response or response from the BPBD which is going better than before, this is also in accordance with their motto, namely fast, responsive and tough.